2017
DOI: 10.29252/arakmu.11.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and Bioconcentration of Cadmium and Copper in Artemia Urmiana Nauplii

Abstract: Background: Artemia urmiana are small crustaceans that because of its non-selective filter feeder pattern potentially may absorb high level of heavy metals through their living environment. In this study, the effects of different levels of cadmium and copper on survival, catalase activity and metals bioconcentration rates in A. urmiana nauplii have been investigated. Methods:The research was carried out in February 2012 at University of Tehran, Tehran, Iran.First experiment was conducted in nine concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…This finding contrasted with that in whole zebrafish and other species [ 56 ]. Previous studies have reported the following LC 50 values of Cu 2+ and Cd 2+ for various species: adult zebrafish, 0.99 μM and 86.1 μM (96-h exposure) [ 57 , 53 ]; kutum ( Rutilus frisii kutum ) fingerlings, 11.6 μM and 211 μM (24-h exposure) [ 58 ]; Artemia urmiana , 470 μM and 703 μM (24-h exposure) [ 59 ]; Rasbora sumatrana (Cyprinidae), 0.852 μM and 12.8 μM (24-h exposure) [ 60 ]; and Poecilia reticulata (guppy) (Poeciliidae), 5.49 μM and 73.0 μM (24-h exposure) [ 60 ], respectively. The higher Cu 2+ tolerance compared with Cd 2+ tolerance found in ZFL was probably because ZFL is a cell line of liver origin, an organ responsible for Cu 2+ elimination.…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasted with that in whole zebrafish and other species [ 56 ]. Previous studies have reported the following LC 50 values of Cu 2+ and Cd 2+ for various species: adult zebrafish, 0.99 μM and 86.1 μM (96-h exposure) [ 57 , 53 ]; kutum ( Rutilus frisii kutum ) fingerlings, 11.6 μM and 211 μM (24-h exposure) [ 58 ]; Artemia urmiana , 470 μM and 703 μM (24-h exposure) [ 59 ]; Rasbora sumatrana (Cyprinidae), 0.852 μM and 12.8 μM (24-h exposure) [ 60 ]; and Poecilia reticulata (guppy) (Poeciliidae), 5.49 μM and 73.0 μM (24-h exposure) [ 60 ], respectively. The higher Cu 2+ tolerance compared with Cd 2+ tolerance found in ZFL was probably because ZFL is a cell line of liver origin, an organ responsible for Cu 2+ elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Cd did not affect the Cu accumulation in zebrafish’s gills [ 28 ]. However, Cd could inhibit on Cu absorption in Artemia Urmiana Nauplii [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…have long been utilized as a convenient bioassay organism because of their availability as cysts, which can easily be stored and hatched out when the need arises. Artemia have been used to assess the toxicity of a wide variety of materials including fungal toxins (Harwig and Scott 1971), organophosphorus insecticides (Sánchez-Fortún et al 1996), chlorinated solvents (Sánchez-Fortún et al 1997), agricultural antibiotics (Migliore et al 1997), phytogenic antibiotics (Kamba and Hasan 2010), cyanobacterial extract (Jaki et al 1999), dental materials (Pelka et al 2000;Milhem et al 2008), marinederived pharmaceuticals (Carballo et al 2002), and trace metals (Brix et al 2003;Kokkali et al 2011;Mohiseni et al 2017). In this study, the in uence of pre-test feeding and initial organism age on the response of Artemia salina to NaBr was evaluated, providing quantitative data on not only the aquatic toxicity of NaBr to a saltwater crustacean, but also for an optimal test design that can be used to minimize the impacts of factors that could confound data interpretation.…”
Section: Introductionmentioning
confidence: 99%